Application of one-handed catches in elite men's team handball - Seipp, D.; Dürselen, J.; Kurth, N.; Nicklas, A. (5th EHF Scientific Conference "Handball for Life", 21.-22.11.2019, Cologne, 2021)
The present study examined the application of one-handed catches in international handball games. Twelve different teams were video analyzed throughout 24 matches. The OHCs were categorized in five categories. Significant differences between the categories itself and some teams were found for the total number of OHCs, for low intense actions and for fast break actions. The average application of OHCs per game was 94.73 ± 30.99.